Cigarette butts: A small but hazardous waste, according to European regulation. (December 2018) - Rebischung, Flore; Chabot, Laure; Biaudet, Hugues; Pandard, Pascal
Highlights: Three cigarette butts samples have been deeply tested and analyzed. CB are classified as hazardous waste, under HP6 (toxicity) and HP14 (ecotoxicity). Calculation and experimental methods for HP14 assessment showed discrepancies. Abstract: The emergence of companies collecting cigarette butts (CB) leads to a new waste stream, exclusively made of butts, whereas they were previously mixed with household and municipal waste. In order to conclude on the classification of this new stream, according to the Waste Framework Directive, three cigarette butts samples were analyzed and submitted to ecotoxicological tests. Hazard properties HP 4 (irritant – skin irritation and eye damage), HP 5 (specific target organ toxicity/aspiration toxicity), HP 6 (acute toxicity), HP 7 (carcinogenic), HP 8 (corrosive), HP 10 (toxic for reproduction), HP 11 (mutagenic) and HP 13 (sensitising) have been assessed by calculation, thanks to the analytical results. HP 14 (ecotoxic) has been evaluated both through calculation method and ecotoxicity tests. Even if the obtained mass balance was not complete, it was still sufficient to classify by calculation CB as hazardous waste, by HP 6 (toxicity), mainly due to their nicotine content. A classification by HP 14 (ecotoxicity) was also determined but only by ecotoxicological tests results, whatever the applied framework (French or "harmonized" test battery). These results highlight the limitation of the classification methodology adopted by European Council which necessitates to identify all compounds to perform a full detailed assessment.